The comparison of Mandibular Cortical Index based on dental status in women using panoramic radiographs - Fitriantika, Gizella; Farizka, Intan; Tanjung, Rizki (Ikatan Radiologi Kedokteran Gigi Indonesia, 2024)
Objectives: The aim of this study is to analyze the difference of the Mandibular Cortical Index (MCI) between dentate and edentulous regions in women using panoramic radiographs. Materials and Methods: This is a comparative analytical observational research with a cross-sectional approach. The samples used were 250 female panoramic radiographs, which were divided into 125 dental region samples and 125 edentulous samples which were available at the Dental Radiology Installation, Dental and Oral Teaching Hospital (RSGM-P) Faculty of Dentistry, Trisakti University. MCI assessment uses i-Dixel software version 2.2.0.3. Morita Japan. The comparative test was carried out using the Mann-Whitney test to determine whether there was a significant difference or not. Results: There is a significant difference in MCI based on dental status with p-value = 0.000 (p <0.05). The percentage of category C1 was found higher (26%) in the dentate group than edentulous group (9,2%), whereas the percentage of category C3 was found higher in the edentulous group (16,3%) than dentate group (3,2%). Conclusion: There is a significant difference in MCI based on dental status with p-value = 0.000 (p <0.05). The percentage of category C1 was found higher (26%) in the dentate group than edentulous group (9,2%), whereas the percentage of category C3 was found higher in the edentulous group (16,3 %) than dentate group (3,2%).